Jefferson County Alabama: a dark cloud looms. Issue 2 (5th May 2016) - Guess, Aundrea Kay; Broom, Lowell; Reburn, James
Abstract : Synopsis: Jefferson County was in a financial crisis as the commissioners faced a decision concerning whether the County should file for bankruptcy. The County was under an EPA mandate to update an outdated and overrunning sewer system. Estimates to do the work ranged from $250 million to $1.2 billion. The situation led to graft, corruption, bribery and illegal activities. More than 20 people were prosecuted in association with the illegal activities involved in financing and construction of the sewer system and four of the five commissioners were sentenced for their involvement in the corruption. Five new commissioners were elected and had to determine what to do after the down-grade of the County's bonds and warrants; the reduced revenues; and the corruption had put the County in a situation where funds were not available to continue to operate the County and provide services to its citizens. Should they declare bankruptcy or choose other paths open to them? Research methodology: Data sources – this case is based on field research and interviews with a commissioner, court documents and from many other public sources. Extent of disguise – the case is not disguised. Relevant courses and levels: The case can be used in graduate or upper division undergraduate courses in accounting, strategy, public administration or finance. There are several topics in the case that could be addressed: governance; economics, government and political issues, ethics, accounting, financial instruments, and strategy.